Long-term outcomes of left atrial appendage closure techniques on stroke prevention of recurrent atrial fibrillation patients: epicardial excision versus percutaneous occlusion - Abibe Goia, Adnan; Xu, Meng; Qiuming, Hu (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study aimed to compare the efficacy of left atrial appendage closure performed by excision (LAAC-EE) vs. occlusion (LAAC-PO) for stroke prevention in patients with recurrent atrial fibrillation undergoing radiofrequency ablation.MethodsIn this retrospective analysis, 160 consecutive patients (109 undergoing LAAC-EE and 51 undergoing LAAC-PO) were evaluated. To adjust for baseline differences, stabilized inverse probability of treatment weighting (IPTW) was applied using a logistic regression model with age, sex, and CHA₂DS₂-VASc score as predictors. Weighted Kaplan–Meier survival analyses were conducted to assess stroke-free survival over a 5-year follow-up period, and weighted Cox proportional hazards regression was used to evaluate the association between LAAC modality and stroke occurrence, adjusting for age, sex, diabetes, CHA₂DS₂-VASc score, HAS-BLED score, and left atrium size.ResultsOverall, the weighted mean CHA2DS2-VASc score was 3.1 ± 0.1 (3.0 ± 0.2 in LAAC-EE vs. 3.3 ± 0.2 in LAAC-PO; p = 0.159), indicating moderate baseline stroke risk. When stratified, 39.2% of LAAC-EE and 18.9% of LAAC-PO patients were in the low-risk category (CHA2DS2-VASc ≤2), 48.2% vs. 69.6% in the medium-risk group (score 3–4), and 12.6% vs. 11.5% in the high-risk group (score ≥5) (p = 0.093). Over 5 years, stroke occurred in 64 patients—29.4% in the LAAC-EE group vs. 62.7% in LAAC-PO—and weighted Kaplan–Meier analysis showed significantly greater stroke-free survival with excision (log-rank p < 0.001). In the weighted multivariate Cox model, LAAC-EE was associated with a non-significant 51.6% reduction in stroke risk (HR 0.48; 95% CI 0.13–1.74; p = 0.27). Age (HR 1.09 per year; p = 0.008) and HAS-BLED score (HR 10.54; p < 0.001) remained significant predictors, whereas sex, diabetes, and CHA₂DS₂-VASc score did not.ConclusionAlthough the multivariate analysis did not achieve statistical significance for the treatment modality, the observed hazard ratio indicates that LAAC-EE may reduce stroke risk by approximately 51.6% compared to LAAC-PO. The significant impact of age and HAS-BLED score on stroke risk underscores the importance of individualized patient selection. These findings suggest a potential clinical benefit of LAAC-EE, particularly among lower-risk patients, and warrant further investigation in larger prospective studies.